EFISIENSI TEKNIS PRODUKSI USAHATANI TEBU PLANT CANE DAN TEBU RATOON CANE (Studi Kasus di PT. Perkebunan Nusantara X) - Intan Kartika Setyawati; Rudi Wibowo (University of Jember, 2019)
The decline in national sugar cane production from 2015 amounted to 2.4 million tons and in 2016 amounted to 2.2 million tons. One of the reason for the decline in sugar cane production is the proportion of Ratoon Cane (RC) which is relatively high compared to Plant Cane (PC). The objective of the study is to analyze the technical efficiency of farming between plant cane (PC) and ratoon cane (RC). The method used in sampling farmer households is purposive by considering there is no sampling frame available in the study area. Data analysis method using the stochastic frontier production function model. The results showed that the plant cane farming (PC) was more technically efficient than ratoon cane (RC) with an average value of PC sugarcane technical efficiency of 93 percent and an average sugarcane technical efficiency of RS by 89 percent.